Jogo Tonggo, Model Pendampingan Belajar dan Bermain Bahasa Inggris pada Anak-Anak Selama Pendemi Di Pare, Kediri - Nurhajati, Diani; Kencanawati, Dewi; Susanti, Yunik; Putri, Octavia Annike (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The Covid-19 pandemic has affected all aspects of life, including the implementation of teaching and learning process at school, from kindergarten up to university. All of the teaching and learning process must be carried out via online to avoid contact with many people, so that it can reduce the spread of the virus. The condition has an impact on the implementation of Rural Community Service (Kuliah Kerja Nyata/KKN) at University of Nusantara PGRI Kediri. The students can carry out the activity in the area where they live. Realizing the fact, the Community Service team adopted the program from the local government of Central Java Province, namely Jogo Tonggo. It is a program, which involves the society to be more aware and care to their neighbors, who have problems dealing with Covid-19. The idea was adopted by the team to share knowledge and experiences with children in the area where the English department student carried out the KKN. The activity was carried out at Tulungrejo Village, Pare District, Kediri. The children in the area, who missed the offline learning, were invited to join the program once a week. They were not only introduced the importance of health protocols, but also played and learned English and other subjects from their school with the student’s guidance. The purpose of the activity is to motivate them to stay enthusiastic about learning, and to reduce their activity of using too much gadget. The output of the program was the compilation of an manual to carry out English activities for children.